Efektivitas Pelayanan E-Samsat Riau Dalam Upaya Peningkatan Penerimaan Pembayaran Pajak Kendaraan Bermotor di Kota Pekanbaru - Balqist Putri Zahrani; Khairul Amri (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Public service is defined as providing services (serving) the needs of people or society who have an interest in the organization in accordance with the basic rules and procedures that have been determined. Therefore, to improve public services, the effectiveness of a service program is needed, where the greater the contribution of the output produced to the specified goals or targets, the more effective the work process of an organizational unit. E-Samsat is an application carried out by the Regional Revenue Agency (BAPENDA) of Riau Province. The aim of this research is to find out how effective the E-Samsat program is in increasing the receipt of motor vehicle tax payments and to find out the inhibiting factors in the implementation of E-Samsat services. This E-Samsat program has several problems, namely network problems so that sometimes it is difficult to access it, platform limitations which can only be accessed via the Play Store. This research method uses descriptive qualitative methods and data collection techniques through primary and secondary data sources obtained through observations, interviews and documentation by researchers and then analyzed. The research results show that the E-Samsat program services have been carried out according to plan, but there is a problem in the banking sector, then related to network problems which still frequently occur, and finally regarding the government's role in responding to the E-Samsat program services.